2016
DOI: 10.32945/atr3819.2016
|View full text |Cite
|
Sign up to set email alerts
|

Energy Productivity and Efficiency of Lowland Rice (Var. PSB Rc18) Under Various Organic Nutrient Sources and Quantum Enhancers

Abstract: Energy analysis is not usually given much emphasis in crop production despite the latter's huge dependence on oil and fuel. This study was conducted for two cropping seasons to assess whether the use of various nutrient sources can increase yield, energy productivity, and use efficiency of lowland rice (PSB Rc18). All production inputs and activities were accounted and energy analysis was done using energy coefficients adopted by previous researchers. Parameters on grain yield, energy expenditures, energy prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Energy inputs on logistics would also increase the price of food delivered in the local markets of Zamboanga City, more so if they are transported far [26]. In the Philippines, the sugar production is an intensive energy-requiring process [29], including inorganic rice production [2,18,26], wheat production [3] and high valued crops [5]. These observations are also true with the nine ( 9) identified dominant AFSs in the uplands of Zamboanga City, where major agricultural crops such as coconut, rubber, banana, upland rice, lanzones and marang (seasonal crops) grown in combination and/or as an inter-crop were becoming energy intensive systems.…”
Section: Total Energy Inputsmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy inputs on logistics would also increase the price of food delivered in the local markets of Zamboanga City, more so if they are transported far [26]. In the Philippines, the sugar production is an intensive energy-requiring process [29], including inorganic rice production [2,18,26], wheat production [3] and high valued crops [5]. These observations are also true with the nine ( 9) identified dominant AFSs in the uplands of Zamboanga City, where major agricultural crops such as coconut, rubber, banana, upland rice, lanzones and marang (seasonal crops) grown in combination and/or as an inter-crop were becoming energy intensive systems.…”
Section: Total Energy Inputsmentioning
confidence: 99%
“…The science of energy accounting in food agriculture has been used as early as 1973 [5] and it has continue to evolved [7,[12][13][14][15][16][17]. In recent years, energy accounting has been used for sugarcane production [2,4,18], rice and cotton [2], wheat [3] and lowland rice [19]. Food sources derived from agroforestry systems (AFSs) such as fruits and annuals as intercrops are sources of caloric energy but to produce such energy also requires enormous energy in the form of machineries, farm implements, equipment, farm tools, various inputs like seeds, fertilizers and chemical pesticides, trucks and other form of logistics used for hauling and transport including labor that are derived from human and draft animal.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that efficient and effective energy use is required for financial savings, fossil resource preservation [32], reduced greenhouse gas emissions from agricultural production systems and energyrelated environmental pollution [33,34], improved agricultural production [31,34,35] and ultimately positive contribution to sustainable development [33,36]. Limited study on energy budgeting in agricultural production systems has been conducted in a few countries, with the majority of studies focusing on cereal crops and cropping system research [37][38][39][40][41][42][43][44][45][46][47][48][49][50]. A few studies from India have also been reported, revealing that the energy consumption pattern varied greatly with agro-climatic zones and energy sources with farmers to engage in agricultural business [51][52][53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%